The challenge in managing working capital in an emerging economy: The case of Bangladesh - Ahkam, Sharif Nurul; Hossain, Syed Asif; Rabby, Sheikh Mohammad; Shorna, Shabnin Rahman; Nahar, Nazmun (Asian Economic and Financial Review, 2024)
The paper seeks to determine whether management can offset an increase in the age of inventory with a reduction in the age of receivables, and which variable is more important in managing the overall cash conversion cycle. Using data from 2011 to 2020 on 77 non-financial companies listed on the Dhaka Stock Exchange, we applied the generalized method of moments regression with a specific goal of examining the impact of receivables and inventory on profitability. When limiting the total amount tied up in working capital is a goal, a legitimate question is whether a firm can limit the total amount tied up in receivables alone, with inventory alone, or net the total reduction. Both variables should have a similar financial cost of working capital. This paper strongly indicates that in managing working capital, the focus needs to be on receivables management. Losing control of receivables will impact profitability much more than managing inventory, and the option to balance an increase in the age of receivables through a decrease in inventory is generally not possible. The results also indicate that larger firms generally do a better job than smaller firms.